ELASMOBRANCH DIVERSITY OF KALIMANTAN WATERS - Fahmi, -; Aldrim, M. (Marine Research in Indonesia, 2007)
A total of 2,310 individuals of elasmobranch fishes consisting of 60 species from 13 families were recorded from survey trips in Kalimantan waters. Six fish landing sites and markets in four provinces of Kalimantan were visited from September 2005 to November 2006. Some new records, endemic and new species were gathered during the surveys. Rays of Dasyatid family were the most common elasmobranch species occurring in this area. Himantura gerrardi, H. uarnak and H. uarnacoides (Dasyatidae) were the most common rays, whereas Chiloscyllium punctatum (Hemiscyllidae), Hemigaleus microstoma (Hemigaleidae), Carcharhinus amblyrhynchoides and C. dussumieri (Carcharhinidae) were the most common sharks recorded during this study. Some endemic and rare species were also recorded including Himantura lobistoma, H. pastinacoides, Pastinachus solocirostris (Dasyatidae) and Glyphis sp. (Carcharhinidae).